The Effect of Camshaft Racing on Matic Motorcycle Performance - Marfizal; Dedi Wardianto; Aliska Jalis (Jurnal Teknik Mesin, 2022)
The research conducted in this paper is related to the Effect of Camshaft Racing on Motor Matic Performance. For Performance Testing such as power, torque, engine speed, acceleration at engine speed of 6000 to 9000 rpm. Performance testing using a dyno test tool type Super Dyno 50L. The results of this test are used to compare the performance of an automatic motorcycle using a standard camshaft (STD) and a Racing camshaft (BRT). From this study it was found that the performance for the Racing camshaft (BRT) increased compared to the standard camshaft performance (STD), the acceleration value was 6.2% to 4.5%, speed 1.0% to 0.6%, power 9.0% to 4.5%. 16.2%, torque 6.1% to 2.9%. In general, it can be said that camshaft Racing (BRT) has better performance.